Protesting for public health: a case for medical activism during the climate crisis. (4th July 2022) - Clery, Philippa; Embliss, Liam; Cussans, Amelia; Cooke, Eleanor; Shukla, Kirsten; Li, Ching
Abstract: Anthropogenic climate change and its sequelae are de-stabilizing our environmental, social, economical and political systems. Not surprisingly, the direct and indirect effects of disrupting these key determinants of health are profoundly detrimental to mental health and wellbeing. Psychiatrists feel compelled to speak out. However, decades of gentle persuasion have failed to invoke sufficient government action so many have turned to activism. Others doubt whether this is, or should be, within their scope of practice. In this article we present the case for medical activism. History has shown prominent activist medics and psychiatrists have been instrumental in creating social and cultural change. We propose that psychiatrists are well-placed to advocate for health issues that cross socio-politico-environmental boundaries. We suggest that, not only do we have a moral imperative to act for the wider determinants of health, but we are also advantageously positioned as trusted professionals with the necessary skills to articulate the problem and advocate for the most vulnerable in society. We call on our training and regulatory bodies to support health activism.